Gas turbine propulsion systems - MacIsaac, Bernie; Langton, Roy. (Hoboken, N.J. : Wiley, 2011)
"'Gas Turbine Propulsion Systems in Aerospace & Defense' pulls together all of the systems and subsystems associated with gas turbine engines in aircraft and marine warship applications. The subject of engine (fuel) control has undergone major changes in the past 20 years due to the advent of the digital electronic control technology and therefore existing books on the subject are typically out of date with current methods. 'Gas Turbine Propulsion Systems in Aerospace & Defense' discusses the latest technologies in this area; including marine propulsion which is an emerging application area for the technology that involves some interesting modifications to aviation technologies. This book also fits well into the systems engineering focus of the Aerospace Series. Includes chapters on aircraft engine systems functional overview, marine propulsion systems, fuel control and power management systems, engine lubrication and scavenging systems, nacelle and ancillary systems, engine certification, unique engine systems and future developments in gas turbine propulsion systems Includes case studies of specific engines Includes applications within marine defence Accompanied by a book companion website featuring full colour images "--
"This book also fits well into the systems engineering focus of the Aerospace Series"--
Front Matter -- Introduction -- Basic Gas Turbine Operation -- Gas Generator Fuel Control Systems -- Thrust Engine Control and Augmentation Systems -- Shaft Power Propulsion Control Systems -- Engine Inlet, Exhaust, and Nacelle Systems -- Lubrication Systems -- Power Extraction and Starting Systems -- Marine Propulsion Systems -- Prognostics and Health Monitoring Systems -- New and Future Gas Turbine Propulsion System Technologies -- Appendix A: Compressor Stage Performance -- Appendix B: Estimation of Compressor Maps -- Appendix C: Thermodynamic Modeling of Gas Turbines -- Appendix D: Introduction to Classical Feedback Control -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Airplanes -- Turbojet engines; Jet boat engines; Vehicles, Military; SCIENCE -- System Theory; TRANSPORTATION -- Aviation -- General; Airplanes -- Turbojet engines; Jet boat engines; Vehicles, Military; Electronic resource; Electronic books